US Prisoners of War in Hiroshima: A 40-Year Investigative Journey of a Japanese Atomic-Bomb Survivor. Issue 1 (2nd January 2019) - Yamaguchi, Hibiki
ABSTRACT: Shigeaki Mori was an eight-year-old child living in Hiroshima when the United States attacked the city with an atomic bomb on 6 August 1945. In this interview, Mori recalls his experience of the bombing. One of the most memorable scenes for him is the cremation of victims in the playground of an elementary school. Thirty years after the bombing, he decided to begin research on the number of cremated corpses in the school. Later, he also conducted an investigation of US prisoners of war who happened to be detained in Hiroshima and experienced the atomic bombing. So far, he has identified 12 US soldiers who were killed by the bomb. In this interview, Mori looks back on how difficult his investigation was. But his efforts bore fruit. President Barack Obama invited him to the speech that the US leader delivered in the Hiroshima Peace Park in May 2016. In the final part of the interview, Mori shares with readers his encounter with the president, his visit to the United States in 2018, and his views on recent developments in nuclear issues.